2022
DOI: 10.1055/a-1754-7309
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of expert center endoscopic assessment of confirmed low grade dysplasia in Barrett’s esophagus diagnosed in community hospitals

Abstract: Background and study aims Optimal management for patients with low-grade dysplasia (LGD) in Barrett’s esophagus (BE) is unclear. According to our national guideline, all patients with LGD with histologic confirmation of the diagnosis by an expert pathologist (i.e. “confirmed LGD”), are referred for a dedicated re-staging endoscopy in an expert center. We aimed to assess the diagnostic value of re-staging endoscopy by an expert endoscopist for patients with confirmed LGD. Methods In this retrospective cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…However recently, in a Dutch cohort of 168 patients with persistent BO-LGD, Nieuwenhuis et al reported visible lesions detected in 7% (n=12) of patients [7]. Whilst Tsoi et al, in a cohort of 75 patients with BO-LGD, identified 18.7% of patients had visible BO-LGD lesions [8].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However recently, in a Dutch cohort of 168 patients with persistent BO-LGD, Nieuwenhuis et al reported visible lesions detected in 7% (n=12) of patients [7]. Whilst Tsoi et al, in a cohort of 75 patients with BO-LGD, identified 18.7% of patients had visible BO-LGD lesions [8].…”
Section: Introductionmentioning
confidence: 98%
“…Majority (64.7%) of visible LGD were flat lesions with abnormal mucosal and vascular patterns. Endoscopic detection of BO-LGD increased over time (38.7% (2009-2012) vs. 54.3% (2018-2022).…”
mentioning
confidence: 98%
“…Advanced endoscopic techniques have significantly improved the morbidity and mortality associated with premalignant conditions (as Barrett’s esophagus) and premalignant lesions (as most large colonic polyps) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the ablative tool should allow complete and sustained endoscopic and histological eradication of all Barrett’s mucosa, be easy to apply, and be safe. Currently, the preferred method for eradication is radiofrequency ablation (RFA) [ 1 , 3 ], in which heat induces necrosis of the target mucosa. However, this technique has some important drawbacks, including the need for expensive material and frequent endoscope reintroduction, usually with an over-the-scope apparatus of challenging use [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Endoscopy, Nieuwenhuis et al address this issue [3]. The authors compared the endoscopic examination performed in a BE expert center with that in a community hospital, in patients referred for flat low grade dysplasia (LGD) that had been confirmed by an expert pathologist.…”
mentioning
confidence: 99%